Teaching and Learning Science Using YouTube Videos and Discovery Learning in Primary School - Koto, Irwan (Mimbar Sekolah Dasar, 2020)
This research aims at comparing the changes in factual, conceptual, and procedural knowledge of heat transfer in learning science using YouTube videos accompanied by discovery learning among fifth graders. A pre-and post-test experimental design was conducted by two different groups. One of the groups was randomly assigned to conduct discovery learning and YouTube videos (n = 21) and the others were to conduct discovery learning and hands-on activities (n = 21). Students in the experimental group used YouTube videos to do the assignments, whereas those in the control group used hands-on activities. Before conducting the treatment, all the students carried out the pre-test. Pre-test analyses showed that there was no significant difference between the two groups in terms of factual, conceptual, and procedural knowledge of heat transfer. The post-test was conducted by students in two groups after completing four weeks throughout the fall semester of the 2018-2019 Academic Year. The research results revealed that both groups showed various effects on the acquisition of factual, conceptual, and procedural knowledge. Well-selected and related video material could enhance student knowledge related to the concept of heat transfer.